Miguel's music - Rivera, Liz; Disney Enterprises (1996-); Disney Storybook Artists; Penguin Random House; Random House Children's Books (New York, NY Random House, 2017)
"Miguel loves music, but his family says it is not allowed. Will he ever change their minds?"--Page [4] of cover
At head of title: Disney-Pixar Coco
2
Keywords: All Souls' Day -- Juvenile fiction; All Souls' Day; Boys -- Mexico -- Juvenile fiction; Boys; Censorship -- Juvenile fiction; Censorship; Dead -- Juvenile fiction; Dead; Families -- Mexico -- Juvenile fiction; Families; Family secrets -- Juvenile fiction; Family secrets; Folklore -- Mexico -- Juvenile fiction; Folklore; Grandparent and child -- Juvenile fiction; Grandparent and child; Guitar -- Juvenile fiction; Guitar; JUVENILE FICTION / Family; JUVENILE FICTION / Holidays & Celebrations; JUVENILE FICTION / Media Tie-In; Manners and customs; Mariachi musicians -- Juvenile fiction; Mariachi musicians; Music -- Juvenile fiction; Music; Musicians -- Juvenile fiction; Musicians; Ghosts -- Fiction; Families -- Fiction; Family life -- Fiction; Music -- Fiction; Musicians -- Fiction; Mexico -- Social life and customs -- Juvenile fiction; Mexico; Fiction; Folk tales; Folk tales; Juvenile works